Analysis of the acoustic field energy distribution in a rectangular hall for many sound sources - TAJCHERT, Maria (Archives of Acoustics, 1981)
This paper presents conclusions regarding the relations of the energy distribution of the field of reflected waves for a simultaneous action of many sources with such parameters as: the dimensions of the hall, the proportion of the dimensions of the floor, and the position of the most powerful sound sources.